Offshore oil . onshore development - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Jim Dinnes, the Deputy Development Officer for the Northeast Scotland Development Authority, speaks with Gerry Anthony of the St. John's Board of Trade and Isaac Davis, MUN Extension Service, on the impact onshore development has had on the city of Aberdeen and the outlying areas.